Science Creativity Assessment Instruments in the Merdeka Curriculum in Elementary Schools - Rahyu Setiani; Rohmatus Syafi'ah; Setyo Hartanto; Ela Rolita Arifianti; Dwikoranto; Syafiah, Rohmatus (AT-THULLAB : Jurnal Pendidikan Guru Madrasah Ibtidaiyah, 2024)
This research is motivated by the alignment between the learning objectives of Natural Sciences (IPA) and the Merdeka curriculum, one of which is to develop student creativity. Therefore, it is necessary to prepare an assessment instrument that can measure student creativity, including creative thinking skills. This research aims to determine whether the assessment instrument to measure creative thinking skills is feasible to use or not. In this research, the approach employed is Research and Development (R&D). The development research method follows the Borg and Gall model. The data collection method uses a questionnaire that is given to validators. The validation sheet is the instrument used. Content validity is the method used for data analysis. The test instrument's validity was high, with Aiken's V score of 0.82, surpassing the 0.800 threshold for high validity. This makes the instrument reliable for assessing students' creative thinking skills. It is suitable for use in elementary schools to evaluate higher-order thinking and creativity. The implications are that the instrument can be applied in elementary schools to assess student learning outcomes at the level of higher-order thinking skills, particularly related to creativity. Guildford's indicators—Fluency, Flexibility, Originality, Elaboration, and Redefinition—offer a comprehensive creativity assessment. Fluency (3 questions) measures idea quantity. Flexibility (2 questions) assesses adaptability to different perspectives. Originality (5 questions) evaluates the uniqueness of ideas. Elaboration (3 questions) examines idea detail. Redefinition (2 questions) measures perspective shifts. All questions are valid, ensuring accurate and thorough creativity evaluation.